La autenticación de firmas manuscritas ante el notario, en documentos que no son escrituras públicas, en el Ecuador - Hormaza Lavayen, Dolores Consuelo (2025)
The article aims to carry out a critical legal analysis of the importance of the authentication of handwritten signatures before the notary in documents that are not public deeds in Ecuador. Through the problematic of the proposed research topic, an exhaustive review of doctrine, jurisprudence and relevant regulations was carried out in order to obtain the historical evolution, theoretical principles and legal practices with reference to the authentication of handwritten signatures in front of the notary in documents that are not public deeds in Ecuador. Through the methodology, this was imminently qualitative seeking to explore the underlying dimensions or fundamental aspects that influence its function, application and its complexities in implementing and understanding in the sphere of Ecuadorian notarial law. The characteristics and principles of signature authentication, including handwritten and electronic signatures in addition to the authentication of public instruments executed abroad, are discussed. It also describes notarial acts and contracts, such as the establishment of legal relationships and the creation, regulation, modification, transfer or termination of rights and obligations. The importance of correctly disseminating the electronic signature authentication service by telematic means and the need to regulate the responsibilities of notaries in notarial activity are highlighted. The article concludes that the authentication of handwritten signatures in front of the notary is essential in order to guarantee the legal certainty that gives validity and legal legitimacy to private documents with the aim of avoiding future legal problems.